2011
DOI: 10.1007/s11837-011-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of novel alumina-based composites for energy efficient sliding systems

Abstract: How would you……describe the overall signifi cance of this paper?The overall signifi cance of this paper is to increase the energy effi ciency, sustainability and applicability of sliding systems by improving the surface properties. This article focuses on development of selflubricating materials with superior surface properties for reduced friction and wear applications.…describe this work to a materials science and engineering professional with no experience in your technical specialty? This article mainly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Effect of Sintering Temperature on Microstructure and Sinterability. It is evident from the optical microscopy [9], and E-SEM study (Fig. 5 a, b, c, d, and e) that grain size of composites decreased with increase in composition of boron for both the sintering temperatures.…”
Section: Thermec 2013mentioning
confidence: 83%
See 2 more Smart Citations
“…Effect of Sintering Temperature on Microstructure and Sinterability. It is evident from the optical microscopy [9], and E-SEM study (Fig. 5 a, b, c, d, and e) that grain size of composites decreased with increase in composition of boron for both the sintering temperatures.…”
Section: Thermec 2013mentioning
confidence: 83%
“…These AlB 2 provided the mechanism for low coefficient of friction. Detailed friction study is reported elsewhere [14], [1]. The matrix phase of Al 2 O 3 was also ensured from XRD results for both sintering temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aluminium based surface composites replacing with Aluminium alloys due to high elastic modulus and improved wear resistance [3][4][5]. The varies surface modification methods are cladding, thermal spray, laser, sintering, electron beam irradiation, coating etc [6][7][8]. Znamirowski et al, (2004) [9] have studied the effect of ceramic particles on the substrate by plasma spraying technique.…”
Section: Introductionmentioning
confidence: 99%